Immediate Full Denture Untuk Perbaikan Estetik dengan Alveolektomi Radikal Pada Rahang Bawah - Vivin Ariestania (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Immediate Denture is once of the Prosthodontics therapy to patients who will be take some tooth extraction in the anterior teeth or sseveral teeth, or even in the exostosis case. Patients who for some reason to have to anterior teeth removed, will experience the aesthetic and psychological disorders. Purpose: The immediate denture intended that the patient does not experience toothless due to tooth extractions and patients can immediately use the artificial tooth immediately without waiting for the healing process. Case: Complete denture will prepare and then it the same time some teeth are planned to be extraction on theworking cast will be remove by cutting it and the complete denture inserted immediately after the extraction teeth and alveolectomy on the patient. Case Management: Control on 3 days, 7 days, 4 weeks, and 8 weeks post-insertion to see the resorption process after tooth extraction, so it maybe need to be relining and rebasing the artificial teeth. 7-day control the healing process already looks better and so with the retention. At 4 weeks after insertion of control, the artificial denture become unstable and it need to be denture relining and rebasing process using a soft liner. At 8 weeks after insertion control, the alveolar ridge has been perfect healing process, and the dentures should be relining and rebasing re-use by self cure acrylic.